2023
DOI: 10.1177/09544089231156074
|View full text |Cite
|
Sign up to set email alerts
|

Wear performance analysis and optimization of process parameters of novel AA7178/nTiO2 using ANN-GRA method

Abstract: The current research investigates the microstructural and wear behaviour of nano TiO2 particles with concentrations of 1%, 2%, and 3%, which were reinforced with an AA7178 metal matrix composite using a stir casting method. Artificial Neural Network (ANN) and Grey Relational Analysis (GRA) methods were used to model the wear characteristics and attain the optimal values of the input process parameters such as load, sliding speed, nanoparticles’ weight percentage, and sliding distance. An L16 orthogonal array w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The obtained adj R square value is 99.96, indicating high reliability of the experimental data and accuracy of the experiment. The confirmation test was conducted for the best combination of 8 g⋅l -1 chromium concentration, 240 µs, and 5 amps current EDM input parameters, and the obtained TWR and SR are 0.198 and 1.56, respectively (Bharat N et al, 2023). The SEM image of aged AA7075 confirmed that TiC reinforcement was uniformly dispersed in the matrix AA7075 material.…”
Section: Optimization Of Edm Parametersmentioning
confidence: 90%
See 3 more Smart Citations
“…The obtained adj R square value is 99.96, indicating high reliability of the experimental data and accuracy of the experiment. The confirmation test was conducted for the best combination of 8 g⋅l -1 chromium concentration, 240 µs, and 5 amps current EDM input parameters, and the obtained TWR and SR are 0.198 and 1.56, respectively (Bharat N et al, 2023). The SEM image of aged AA7075 confirmed that TiC reinforcement was uniformly dispersed in the matrix AA7075 material.…”
Section: Optimization Of Edm Parametersmentioning
confidence: 90%
“…The constituents of Keller's reagent were 2.5 ml HNO 3 , 1.5 ml HCl, 1 ml HF and 95 ml Distilled Water (Kumar et al, 2023). The enhancement of micro hardness causes it to be very hard to machine, and hence the determination of the optimized parameters of machining is needed (Bharat and Bose, 2023). The EDM parameters were optimized for best aged AA7075/TiC composite.…”
Section: Elements Ti Mg Fe Si Cr Zn Mn Cu Almentioning
confidence: 99%
See 2 more Smart Citations